2018
DOI: 10.1016/j.matchar.2017.12.020
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure characterisation and mechanical properties of a functionally-graded NbC/high chromium white cast iron composite

Abstract: A functionally graded NbChigh chromium white cast iron composite was successfully fabricated by centrifugal casting for high wear applications. The migration of primary NbC particles to the outer periphery, as predicted by Stokes' law, resulted in an extremely hard outer layer at the surface of a softer bulk material. Microstructural characterisation showed that both the volume fraction and the morphology of the carbides varies along the thickness of the specimen. At the outer surface, the NbC was present as p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…A comparison between the expected fracture toughness results in Table 1 and the actual fracture toughness results reported in Table 2 shows that the hard layer performed below expectations while the bulk material performed within the expected range. A detailed explanation for this, based on detailed fracture surface analysis and microstructural characterisation, is also provided in the study of the parent material from which the specimens were obtained from [ 18 ]. What is important, however, is that the fracture toughness results of both the hard layer and the bulk material, as calculated using the proposed DIC and photogrammetry technique, were consistent with those of traditional high chromium white cast iron alloys (20 MPa to 33 MPa as reported earlier).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A comparison between the expected fracture toughness results in Table 1 and the actual fracture toughness results reported in Table 2 shows that the hard layer performed below expectations while the bulk material performed within the expected range. A detailed explanation for this, based on detailed fracture surface analysis and microstructural characterisation, is also provided in the study of the parent material from which the specimens were obtained from [ 18 ]. What is important, however, is that the fracture toughness results of both the hard layer and the bulk material, as calculated using the proposed DIC and photogrammetry technique, were consistent with those of traditional high chromium white cast iron alloys (20 MPa to 33 MPa as reported earlier).…”
Section: Resultsmentioning
confidence: 99%
“…In summary, this mechanical test requires the fabrication of fatigue pre-cracked notched specimens. A detailed study of the investigated material is reported elsewhere [ 18 ], but all relevant information pertaining to this study (namely, a summary of the material and the three-point bending test procedures and results) will be detailed here. The schematic of the three-point bending set-up is shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, due to their higher dispersion and lower fraction, when compared to layer I, they did not cause increased micro-delamination. This layer (Figure 12b) was dominated by the micro-cutting mechanism (scratches), and the niobium carbides firmly embedded in the eutectic matrix were visible, which, similar to work [36], inhibited abrasive wear. The favorable effect of NbC on abrasive wear was also confirmed in [20][21][22][23]37].…”
Section: Topography Of the Worn Surfacementioning
confidence: 92%
“…Compared with the complex preparation process of continuous gradient materials, the metal-based functionally gradient composites with relatively simple preparation process [ 15 ] will be one of the development directions of laminated gradient materials. Metal-based functionally gradient composites have specific positional properties in components, in addition to performing their specific properties, metal-based functionally gradient composites are often required to withstand high stress or load in structures or components.…”
Section: Introductionmentioning
confidence: 99%